The possibilities of lung perfusion scintigraphy in the diagnosis of pulmonary embolism and chronic thromboembolic pulmonary hypertension - V.Yu. Kundin; M.V. Satyr; I.V. Noverko; A.V. Khokhlov (Кардіохірургія та інтервенційна кардіологія)
Methods of the radiation diagnosis of pulmonary embolism and chronic thromboembolic pulmonary hypertension are reviewed in this article; the comparison, advantages and limitations of these methods are discussed. The principle of lung perfusion scintigraphy and its differences from other radiation examinations are described. The place of lung perfusion scintigraphy in the contemporary diagnostic protocols has been determined. The important advantages of this method are high sensitivity, high negative predictive value, non-invasiveness, safety and low radiation exposure. The technique, regimes and evaluation of lung perfusion scintigraphy results are described. We present clinical cases with usage of lung perfusion scintigraphy. Conclusions about its efficiency and application instructions have been obtained.